A novel approach for flotation recovery of spodumene, mica and feldspar from a lithium pegmatite ore. (10th February 2018) - Tian, Jia; Xu, Longhua; Wu, Houqin; Fang, Shuai; Deng, Wei; Peng, Tiefeng; Sun, Wei; Hu, Yuehua
Abstract: In this paper, a complete scheme aimed at improving the flotation performance of spodumene and comprehensively recycling mica and feldspar from lithium tailings in an economical and environmentally friendly way is put forward. The flotation performance of spodumene and feldspar with four size ranges (0–19, 19–38, 38–45 and 45–75 μm) are investigated in single mineral micro-flotation tests. The results show that the maximum spodumene recovery is obtained with coarse particles of 38–45 μm, while for feldspar, the best flotation performance is found with fine particles of 0–19 μm. In condition tests, the optimum dose of mixed collector SX is found to be 1600 g/t. The optimum doses of the regulators Na2 CO3, NaOH and CaCl2 are selected as 800, 800 and 300 g/t, respectively, by orthogonal tests. Based on the single mineral micro-flotation and condition experiment results, three flowsheets are designed to produce qualified spodumene products in batch flotation tests. After comparison, the flowsheet-C is recommended, which improves the grade and recovery of Li2 O in spodumene concentrates to 6.02% and 87.34%, respectively. This paper also puts forward an environmentally friendly flotation flowsheet aimed at recycling feldspar in spodumene tailings, through which K2 O + Na2 O has a grade and recovery of 11.33% and 61.33%, respectively, in the feldspar concentrates. By adopting the flowsheets presented in the paper, nearly 70% of raw lithium pegmatite ore is translated into qualified mica, spodumene and feldspar products to realize a comprehensive utilization of the resource. The brief economic analysis further confirms that the new scheme has greater economic potential than the commonly used one. Graphical abstract: Image 1 Highlights: The flotation recoveries of single minerals of different sizes were determined. The optimum dosage of reagents was selected by orthogonal tests. Three flotation flowsheets were designed to improve flotation indexes. Comprehensive utilization of the lithium pegmatite ore was realized.